Lack of riluzole efficacy in the progression of the neurodegenerative phenotype in a new conditional mouse model of striatal degeneration - Kreiner,Grzegorz; Rafa-Zabłocka,Katarzyna; Chmielarz,Piotr; Bagińska,Monika; Nalepa,Irena (PeerJ, 2017)
Background Huntington’s disease (HD) is a rare familial autosomal dominant neurodegenerative disorder characterized by progressive degeneration of medium spiny neurons (MSNs) located in the striatum. Currently available treatments of HD are only limited to alleviating symptoms; therefore, high expectations for an effective therapy are associated with potential replacement of lost neurons through stimulation of postnatal neurogenesis. One of the drugs of potential interest for the treatment of HD is riluzole, which may act as a positive modulator of adult neurogenesis, promoting replacement of damaged MSNs. The aim of this study was to evaluate the effects of chronic riluzole treatment on a novel HD-like transgenic mouse model, based on the genetic ablation of the transcription factor TIF-IA. This model is characterized by selective and progressive degeneration of MSNs. Methods Selective ablation of TIF-IA in MSNs (TIF-IAD1RCre mice) was achieved by Cre-based recombination driven by the dopamine 1 receptor (D1R) promoter in the C57Bl/6N mouse strain. Riluzole was administered for 14 consecutive days (5 mg/kg, i.p.; 1× daily) starting at six weeks of age. Behavioral analysis included a motor coordination test performed on 13-week-old animals on an accelerated rotarod (4–40 r.p.m.; 5 min). To visualize the potential effects of riluzole treatment, the striata of the animals were stained by immunohistochemistry (IHC) and/or immunofluorescence (IF) with Ki67 (marker of proliferating cells), neuronal markers (NeuN, MAP2, DCX), and markers associated with neurodegeneration (GFAP, 8OHdG, FluoroJade C). Additionally, the morphology of dendritic spines of neurons was assessed by a commercially available FD Rapid Golgi Stain™ Kit. Results A comparative analysis of IHC staining patterns with chosen markers for the neurodegeneration process in MSNs did not show an effect of riluzole on delaying the progression of MSN cell death despite an observed enhancement of cell proliferation as visualized by the Ki67 marker. A lack of a riluzole effect was also reflected by the behavioral phenotype associated with MSN degeneration. Moreover, the analysis of dendritic spine morphology did not show differences between mutant and control animals. Discussion Despite the observed increase in newborn cells in the subventricular zone (SVZ) after riluzole administration, our study did not show any differences between riluzole-treated and non-treated mutants, revealing a similar extent of the neurodegenerative phenotype evaluated in 13-week-old TIF-IAD1RCre animals. This could be due to either the treatment paradigm (relatively low dose of riluzole used for this study) or the possibility that the effects were simply too weak to have any functional meaning. Nevertheless, this study is in line with others that question the effectiveness of riluzole in animal models and raise concerns about the utility of this drug due to its rather modest clinical efficacy.
Keywords: Riluzole; Neurodegeneration; Huntington’s disease; Transgenic models; Neurogenesis; Neuroprotection